Rancang Bangun Inverter Sederhana (IS) dengan Memanfaatkan IC 555 sebagai Pembangkit Tegangan Pada Mata Kuliah Elektronika I - Saputro, Handoyo; Erlangga, Sony Yunior; Winingsih, Puji Hariati (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2021)
The development of the industrial world in the current porous era, which continues to develop in various fields, certainly makes human life easier and full of challenges. In line with the rapid industrial progress, the need for electricity as an energy source is increasing. One of the household electricity needs is the use of an inverter which functions to convert 12 Volt DC voltage into 220 Volt 50 Hz AC voltage. This inverter functions as a backup electricity provider for both vehicles and household needs, as emergency power when the household electricity goes out. In this study, a Simple Inverter (IS) device will be made using IC 555 as a voltage generator needed in Electronics I learning, in which students learn about concepts and their applications. The purpose of this research is the design of IS teaching aids used to increase the voltage in the physics learning of Electronics I by determining the input power and output power. This type of research is development using a 4-D development model. The results of the IS tool test with product feasibility tests from 2 media experts and material experts with an average score of 4.64 or 94.2% and responses from 4 students with an average score of 4.73 or 95.8% so that it is included in the very good category. The average measured input power (63.0 ± 0.5) Wh and the resulting output power IS Innovation (2191 ± 0.5) Wh which means IS works at a Power Gain of 34.8 on a 5 Ah 12 V motor ACCU, with The power capacity used per 60 W is around 15.5 minutes and for ACCU 60 Ah 12 Volt it is around 3.1 hours